SIGABIM: a framework for BIM application - André Monteiro (2012)
Building Information Modeling tools are slowly but steadily becoming a recurring tool for architectural and engineering design. As contractors realize that BIM also provides benefits when adopted for the construction phase, the need for dynamic ways of exchanging information between different models, of different specialties, during different phases of the project, becomes increasingly important. The IFC format is usually pointed as the best solution for interoperability issues, however, it is not a one hundred per cent reliable platform for exchanging data between BIM models; it must me complimented with a dynamic, standardized, framework for BIM application that addresses interoperability and defines protocols for adequate information management within a BIM flow. This article elaborates on the problematic of BIM frameworks, while also presenting key aspects and findings of the research project SIGABIM.